Ferritic stainless steel and method for manufacturing the same

CN118076759BActive Publication Date: 2026-10-09NIPPON STEEL STAINLESS STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280067974.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-09
Filing Date
2022-12-01
Publication Date
2026-10-09
Estimated Expiration
2042-12-01

AI Technical Summary

Benefits of technology

[0019]根据本发明的一方案,能够实现具有耐氧化性且具有比以往优异的钎焊性的铁素体类不锈钢。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118076759B_ABST
    Figure CN118076759B_ABST
Patent Text Reader

Abstract

The ferrite stainless steel according to one aspect of the present invention contains, in mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the remainder consists of Fe and inevitable impurities, and has an Al-based oxide film of 8 nm or more and less than 20 nm on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to ferritic stainless steel and its manufacturing method. Background Technology

[0002] Ferritic stainless steels containing high levels of Al are widely used for various heat-resistant applications in automobiles or two-wheeled vehicles, such as catalyst carriers (including electrically heated ones), equipment, and combustion towers, due to their resistance to high-temperature oxidation.

[0003] Patent document 1 discloses that when the thickness of the oxide film of Al2O3 columnar crystals is 0.1 μm or more and 1.0 μm or less, it is possible to manufacture Fe-Cr-AL alloy foil that can fully exert the effects of oxidation resistance and high temperature deformation resistance.

[0004] Patent document 2 discloses that stainless steel foil with excellent diffusion bonding and brazing properties can be produced when the thickness of the Al2O3 film is 20 nm or more and 200 nm.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-105506

[0008] Patent Document 2: Japanese Patent Application Publication No. 2011-32524 Invention Overview

[0010] The problem that the invention aims to solve

[0011] However, while the technologies disclosed in Patent Documents 1 and 2 may be considered effective in terms of oxidation resistance, there is a problem of low brazingability when these technologies are applied to products requiring brazing properties, such as catalyst supports.

[0012] One aspect of the present invention aims to achieve ferritic stainless steel with oxidation resistance and superior brazing properties compared to the past.

[0013] Technical solutions for solving the problem

[0014] To address the aforementioned issues, one aspect of the present invention relates to a ferritic stainless steel, which, by mass percent, contains C: less than 0.030%, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: less than 0.050%, S: less than 0.005%, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: less than 1.00%, Nb: 0.01 to 0.70%, N: less than 0.030%, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the remainder consisting of Fe and unavoidable impurities, and has an Al-based oxide film on its surface of 8 nm or more and less than 20 nm.

[0015] Furthermore, one aspect of the present invention relates to a method for manufacturing ferritic stainless steel, which contains, by mass percent, C: 0.030% or less, Si: 0.01-1.5%, Mn: 0.01-1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0-25.0%, Al: 2.0-4.0%, Ni: 1.00% or less, Nb: 0.01-0.70%, N: 0.030% or less, B: 0.0003-0.01%, REM: 0.01-0.20%, with the remainder consisting of Fe and unavoidable impurities.

[0016] This includes the cold rolling process and the final annealing process following the cold rolling process.

[0017] The final annealing process includes a first step of heating to a temperature range of 900°C to 1200°C under an inert gas atmosphere and at a dew point below -40°C.

[0018] Invention Effects

[0019] According to one aspect of the present invention, it is possible to achieve ferritic stainless steel with oxidation resistance and superior brazing properties compared to the past. Attached Figures

[0020] Figure 1 This is a SEM image showing a cross-section of an alumina layer, mainly composed of alumina, formed when ferritic stainless steel according to one embodiment of the present invention is heated at 1050°C for 50 hours.

[0021] Invention Embodiments

[0022] The following is a detailed description of one embodiment of the present invention. In this specification, the term "stainless steel" refers to stainless steel material of any shape without limitation. Examples of such stainless steel material include steel plates, steel pipes, and steel bars. Furthermore, in this specification, the unit "%" for the content of each component element, unless otherwise specified, means "mass %". Also, in this specification, "A to B" indicates A or more and B or less.

[0023] (Composition of ferritic stainless steel)

[0024] First, the necessary elements constituting the ferritic stainless steel in this embodiment will be explained.

[0025] One embodiment of the present invention relates to a ferritic stainless steel, which, as a steel composition, contains, by mass %: C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.

[0026] Compared to conventional ferritic stainless steels containing high levels of Al, this composition exhibits a lower Al content. An embodiment of the present invention provides a ferritic stainless steel with the aforementioned composition, resulting in a ferritic stainless steel with excellent toughness.

[0027] The significance of the content of each element in the ferritic stainless steel according to one embodiment of the present invention will be explained below. Furthermore, this ferritic stainless steel, in addition to the components shown below, is composed of iron (Fe) or unavoidably mixed small amounts of impurities (unavoidable impurities).

[0028] <C: Carbon>

[0029] C is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, with increasing C content, abnormal oxidation becomes more likely. Furthermore, excessive C content deteriorates the toughness of slabs and hot-rolled coils, making it difficult to process into sheets through hot working. Therefore, in one aspect of the present invention, the upper limit of C content is specified as 0.030%. Setting the C content to 0.020% or less further reduces the possibility of abnormal oxidation and improves processability. For the above reasons, a more preferred C content is 0.002 to 0.015%.

[0030] <Si: Silicon>

[0031] Si is an effective element for improving oxidation resistance and is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, excessive Si content may reduce toughness and workability. Therefore, in one aspect of the present invention, the Si content is 0.01 to 1.50%. By setting the Si content to 0.01 to 1.0%, more preferably 0.01 to 0.50%, its effect as a deoxidizer and workability are further improved.

[0032] <Mn: Manganese>

[0033] Mn is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, if the Mn content is excessive, it may destabilize the ferrite phase and reduce its resistance to high-temperature oxidation. Therefore, in one aspect of the present invention, the Mn content is 0.01 to 1.00%. By setting the Mn content to 0.01 to 0.80%, and more preferably 0.01 to 0.50%, the possibility of corrosion initiation is further reduced.

[0034] <P: Phosphorus>

[0035] P is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, excessive P content may lead to deterioration of oxidation resistance and hot-rolled sheet toughness. Therefore, in one aspect of the present invention, the P content is specified to be 0.050% or less. By setting the P content to 0.040% or less, the deterioration of processability can be further reduced. For the above reasons, a more preferred P content is 0.005 to 0.030%.

[0036] <S: Sulfur>

[0037] S is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, if the S content is excessive, it may adversely affect the formation of the Al2O3 film in the ferritic stainless steel, potentially deteriorating its oxidation resistance. Therefore, in one aspect of the present invention, the S content is specified to be 0.005% or less. For the above reasons, a more preferred S content is 0.0001 to 0.002%.

[0038] <Cr: Chromium>

[0039] Cr is a fundamental alloying element essential for improving the high-temperature oxidation resistance of ferritic stainless steel. By containing a specified amount or more of Cr, an oxide film forms on the surface of the stainless steel, thus inhibiting oxidation. On the other hand, excessive Cr content reduces toughness and deteriorates manufacturability. Therefore, in one aspect of the present invention, the Cr content is specified as 15.0% to 25.0%. By setting the Cr content to 16.0% to 22.0%, and more preferably 17.0% to 20.0%, the oxidation inhibition effect and manufacturability can be further improved.

[0040] <Al: Aluminum>

[0041] Al is a fundamental alloying element essential for improving the high-temperature oxidation resistance of ferritic stainless steel. By containing a specified amount or more of Al, an Al₂O₃ oxide film forms on the surface of the stainless steel, thus inhibiting oxidation. Furthermore, the addition of REM or Y not only makes the oxide film denser but also improves adhesion to the base steel, suppressing abnormal oxidation. On the other hand, excessive Al content degrades the toughness of the stainless steel, resulting in poor manufacturability and processability. Therefore, in one aspect of the present invention, the Al content is specified as 2.0% to 4.0%. Setting the Al content to 2.5% to 3.7%, and more preferably 2.8% to 3.5%, further improves the high-temperature oxidation resistance and manufacturability.

[0042] <Ni:Nickel>

[0043] Ni is an element that improves the corrosion resistance of ferritic stainless steel and is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, if the Ni content is excessive, the ferrite phase becomes unstable, and the material cost increases. Therefore, in one aspect of the present invention, the Ni content is specified to be 1.00% or less. By setting the Ni content to 0.50% or less, it is possible to further suppress the instability of the ferrite phase and the increase in manufacturing costs caused by excessive Ni content. For the above reasons, a more preferred Ni content is 0.02% to 0.30%.

[0044] <N: Nitrogen>

[0045] Nitrogen (N) is an essential element in the ferritic stainless steel according to one embodiment of the present invention. However, if it is present in excess, it may combine with Al in the steel to form AlN, potentially becoming a starting point for accelerated oxidation. Therefore, in one aspect of the present invention, the N content is specified to be 0.030% or less. By setting the N content to 0.025% or less, the possibility of hardening can be further reduced. For the above reasons, a more preferred N content is 0.003 to 0.020%.

[0046] <Nb (Niobium), B (Boron), REM (Rare Earth Elements)>

[0047] Nitrogen (Nb) is an element added to ensure high-temperature strength. Nb also promotes the formation of an Al₂O₃ film. Furthermore, it reduces grain size and increases grain boundary area by inhibiting recrystallization in stainless steel. On the other hand, excessive Nb content can lead to a deterioration in the toughness of hot-rolled steel.

[0048] Boron (B) is an element that improves the secondary workability and oxidation resistance of shaped articles made from ferritic stainless steel. On the other hand, if B is present in excess, B compounds become inclusions (impurities).

[0049] REM (rare earth metals) refers to the lanthanide elements (La, Ce, Pr, Nd, Sm, etc., with atomic numbers 57-71). REM elements improve resistance to high-temperature oxidation. By containing a specified amount or more of REM, the Al oxide film is stabilized. Furthermore, it improves oxidation resistance by enhancing the adhesion between the base material and the oxide. On the other hand, excessive REM content can cause surface defects during hot rolling, reducing manufacturability.

[0050] Based on the above reasons, in one aspect of the present invention, the Nb content is specified as 0.01 to 0.70%. By setting the Nb content to 0.05 to 0.50%, more preferably 0.08 to 0.30%, the possibility of processability degradation can be further reduced, and oxidation resistance can be improved. The upper limit of the Nb content is further preferably 0.20% or 0.15%. Furthermore, the B content is specified as 0.0003 to 0.01%. By setting the B content to 0.0003 to 0.005%, the presence of inclusions can be further reduced, and secondary processability can be improved. Furthermore, the REM content is specified as 0.01 to 0.20%. The REM content is preferably 0.02 to 0.15%, more preferably 0.04 to 0.10%.

[0051] (Other ingredients)

[0052] The ferritic stainless steel according to one aspect of the present invention may further contain at least one element selected from Zr, V, Cu, Mo, W, Hf, Sn, Ta, Ti, Mg, and Ca as elements other than those mentioned above.

[0053] <Zr: Zirconium>

[0054] Zr is an element that improves oxidation resistance. On the other hand, if excessive Zr is added, it may cause the steel to harden, leading to a decrease in toughness. Therefore, in one aspect of the present invention, it may contain 0.50% or less of Zr. Considering the reduction in hardening, the Zr content is more preferably 0.01 to 0.40%.

[0055] <V: Vanadium>

[0056] V is an element that improves workability and weld toughness. On the other hand, if too much V is added, there is a possibility that the toughness of the hot-rolled sheet will deteriorate. In one aspect of the present invention, V may be contained at 0.50% or less. Considering the reduction in hardening, the V content is more preferably 0.02 to 0.35%.

[0057] <Cu: Copper>

[0058] Cu is an element that improves the corrosion resistance of ferritic stainless steels. On the other hand, excessive Cu content may lead to a decrease in oxidation resistance and hot workability. Therefore, in one aspect of the present invention, the Cu content may be less than 1.0%. Considering material costs, the Cu content is more preferably 0.01 to 0.5%.

[0059] <Mo:Molybdenum>

[0060] Mo is an element that improves corrosion resistance. On the other hand, excessive Mo content leads to hardening, reduced toughness, and increased material costs. Therefore, in one aspect of the present invention, the content may be 2.0% or less of Mo. Considering processability, material costs, etc., the Mo content is more preferably 0.01% to 1.0%.

[0061] <W: Tungsten>

[0062] W is an element added to ensure high-temperature strength. On the other hand, excessive W content degrades the toughness of the hot-rolled sheet and increases material costs. Therefore, in one aspect of the present invention, the W content may be less than 2.0%. Considering material costs, the W content is more preferably 0.01 to 1.0%.

[0063] <Hf: Hafnium>

[0064] Hf is an element that improves oxidation resistance. On the other hand, excessive Hf content reduces the toughness of hot-rolled steel sheets and increases material costs. Therefore, in one aspect of the present invention, the Hf content may be less than 0.50%. Considering both toughness and material costs, the Hf content is more preferably 0.001 to 0.20%.

[0065] <Sn: Tin>

[0066] Tin (Sn) is an element that improves the corrosion resistance of ferritic stainless steels. On the other hand, excessive Sn content reduces processability and increases material costs. Therefore, in one aspect of the present invention, the Sn content may be 0.50% or less. Considering processability, cost, etc., the Sn content is more preferably 0.005% to 0.20%.

[0067] <Ta: Tantalum>

[0068] Ta is an element that improves the cleanliness and oxidation resistance of steel. On the other hand, excessive Ta content reduces toughness and increases material costs. Therefore, in one aspect of the present invention, the content of Ta may be 0.5% or less. Considering toughness and material costs, the Ta content is preferably 0.40% or less. For the above reasons, a more preferred Ta content is 0.001 to 0.30%.

[0069] <Ti: Titanium>

[0070] Ti, through reaction with C and / or N, can transform ferritic stainless steel into a ferritic monolayer at 900–1000 °C. On the other hand, excessive Ti content may lead to the formation of TiO2 in Al oxides, potentially degrading the oxidation life. Therefore, in one embodiment of the present invention, Ti content of 0.20% or less may be included. Considering factors such as processability, a Ti content of 0.005–0.15% is more preferable.

[0071] <Mg: Magnesium>

[0072] In molten steel, Mg forms Mg oxide with Al, acting as a deoxidizer. However, excessive Mg content reduces the toughness and manufacturability of the steel. Therefore, in one aspect of the present invention, Mg may be present in amounts of 0.015% or less. For the above reasons, the preferred Mg content is 0.0002% to 0.0080%.

[0073] <Ca: calcium>

[0074] Ca is an element that improves hot workability. On the other hand, if the Ca content is excessive, the toughness and manufacturability of the steel decrease. Therefore, in one aspect of the present invention, the Ca content may be less than 0.015%. For the above reasons, the preferred Ca content is 0.0001 to 0.012%.

[0075] In this embodiment, the ferritic stainless steel can also satisfy [Al] / (10×[Nb]) < 8 when [Al] is set as Al by mass% and [Nb] is set as Nb by mass%. The inventors have discovered that an optimal amount of Nb needs to be added, corresponding to the amount of Al added, and by satisfying the above formula, various properties such as oxidation resistance shown in the following embodiments can be satisfied.

[0076] (Al-based oxide film)

[0077] Next, the Al-based oxide film on the surface of the ferritic stainless steel involved in this embodiment will be described.

[0078] The ferritic stainless steel in this embodiment has an Al-based oxide film on its surface with a thickness of 8 nm or more and less than 20 nm. This Al-based oxide film is primarily composed of aluminum oxide and is formed through a final annealing process described later. More specifically, the Al-based oxide film involved in this disclosure refers to a film with an Al concentration of 10% or more. By having an Al-based oxide film with a thickness of 8 nm or more, the ferritic stainless steel of this embodiment exhibits oxidation resistance. Furthermore, by having an Al-based oxide film thickness of less than 20 nm, ferritic stainless steel with excellent brazing properties can be achieved.

[0079] (Alumina layer)

[0080] Through in-depth research, the inventors discovered that when Nb and REM are included as essential elements in a suitable concentration range in ferritic stainless steel, the columnar crystallization of the alumina layer formed under service conditions is enhanced. This can be attributed to the concentration of Nb and REM at the grain boundaries of the alumina layer. Furthermore, it was found that including B as an essential element in a suitable concentration range also enhances columnar crystallization.

[0081] The ferritic stainless steels disclosed herein are suitable for applications requiring high-temperature oxidation resistance. Therefore, the aforementioned usage conditions refer to high-temperature conditions. For example, in this embodiment, an alumina layer 20 formed by heating at 1050°C for 50 hours will be described.

[0082] The ferritic stainless steel involved in this embodiment contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.

[0083] The alumina layer 20 formed by heating ferritic stainless steel containing the above-mentioned components at 1050°C for 50 hours has the following characteristics. That is, when (C) is set as the thickness of columnar crystals in the cross section when the alumina layer 20 is cut in the thickness direction, and (E) is set as the thickness of equiaxed crystals in the cross section when the alumina layer 20 is cut in the thickness direction, the following formula (1) is satisfied or the columnar crystals are 100%.

[0084] (C) / (E)≥1.2···(1)

[0085] Figure 1This is a SEM image showing a cross-section of an alumina layer 20, which is mainly composed of alumina, formed by heating a ferritic stainless steel 1 at 1050°C for 50 hours according to an embodiment of the present invention.

[0086] like Figure 1 As shown, if a ferritic stainless steel with an Al-based oxide film is heated at 1050°C for 50 hours, an alumina layer 20, mainly composed of alumina, is formed in the ferritic stainless steel 1. The alumina layer 20 has columnar crystals 201 and equiaxed crystals 202.

[0087] Columnar crystals 201 are a texture of elongated grains growing along the thickness of the alumina layer 20. Equiaxed crystals 202 are a polycrystalline texture in which the shape and orientation of the grains constituting equiaxed crystals 202 are isotropic. Figure 1 The symbol C in the figure represents the thickness of the columnar crystals in the cross section when the alumina layer 20 is cut in the thickness direction. Figure 1 The symbol E in the figure represents the thickness of the equiaxed crystals in the cross section when the alumina layer 20 is cut in the thickness direction.

[0088] Since the grain boundary density of equiaxed crystal 202 is greater than that of columnar crystal 201, the oxygen diffusion path at the grain boundaries is increased. Therefore, the oxidation lifetime of equiaxed crystal 202 is shorter than that of columnar crystal 201. The ferritic stainless steel involved in this embodiment has excellent oxidation resistance under high temperature conditions because the alumina layer 20 satisfies the above formula (1) or is 100% columnar.

[0089] (Manufacturing method)

[0090] First, an example of the manufacturing process of ferritic stainless steel in this embodiment will be briefly described. The manufacturing process of ferritic stainless steel in this embodiment includes, in sequence, a pretreatment process, a hot rolling process, an annealing process, a first pickling process, a cold rolling process, an intermediate annealing process, a final annealing process, and a second pickling process.

[0091] In the pretreatment process, firstly, steel with its composition adjusted to the scope of this invention is melted in a melting furnace under a vacuum or argon atmosphere, and then cast to produce a slab. Next, hot-rolled slab sheets are cut from the slab. Then, the slab sheets are heated in atmospheric atmosphere to a temperature range of 1100°C to 1300°C. There is no limitation on the time for heating and holding the slab sheets. Furthermore, in the case of industrially performed pretreatment processes, the casting can be continuous casting.

[0092] The hot rolling process is a process of producing hot-rolled steel strip of a specified thickness by hot rolling a slab (steel block) obtained in the pretreatment process.

[0093] The annealing process is a process that softens the hot-rolled steel strip obtained in the hot rolling process by heating it to, for example, 900–1050°C. This annealing process is performed as needed and may or may not be performed.

[0094] The first pickling process is a process of washing away the oxide scale adhering to the surface of the annealed steel strip obtained by the above-mentioned annealing process using a pickling solution such as hydrochloric acid or a mixture of nitric acid and hydrofluoric acid.

[0095] The cold rolling process is a process of further thinning the annealed steel strip, which has had its oxide scale removed in the first pickling process. The reduction rate in the cold rolling process is, for example, 50% to 90%.

[0096] The intermediate annealing process is a process that softens the steel strip obtained in the cold rolling process by heating it to, for example, 900–1050°C. This annealing process is performed as needed and may or may not be performed.

[0097] In the manufacturing method of ferritic stainless steel according to this embodiment, a final annealing process is included after intermediate annealing (after the cold rolling process). In the final annealing process, as a first process, a heating process is performed in an inert gas atmosphere at a dew point below -40°C, within a temperature range of 900°C to 1200°C. Following this first process, as a second process, a process can also be performed in an inert gas atmosphere at a dew point below -40°C, maintaining the temperature in the range of 900°C to 1200°C for a time of no more than 5 minutes. Through this final annealing process, ferritic stainless steel with an Al-based oxide film of 8 nm or more and less than 20 nm on the surface can be manufactured.

[0098] Here, the inert gas can be, for example, Ar, H2, or N2. Alternatively, the inert gas can be a mixture of two or three of Ar, H2, and N2 in the range of 1% to 99% to form a 100% gas. More specifically, the inert gas can also be, for example, a mixture of hydrogen with nitrogen and / or argon, in which case it contains 70% to 90% hydrogen, or it can contain 10% to 30% nitrogen or argon, or it can contain 5% to 25% nitrogen and argon to make the nitrogen and argon content 30%.

[0099] The second pickling process is a process in which the oxide scale adhering to the surface of the steel strip obtained in the final annealing process is washed away using a pickling solution such as a mixture of nitric acid and hydrofluoric acid, as needed.

[0100] (Summarize)

[0101] The ferritic stainless steel disclosed in Scheme 1 contains, by mass percent, less than 0.030% C, less than 0.01% Si, less than 1.5% Mn, less than 1.00% P, less than 0.05% S, less than 0.005% Cr, less than 15.0% Al, less than 4.0% Ni, less than 1.00% Nb, less than 0.01% N, less than 0.03% B, less than 0.0003% REM, less than 0.01% REM, and the remainder consists of Fe and unavoidable impurities, and has an Al-based oxide film of more than 8 nm and less than 20 nm on the surface.

[0102] Based on the above composition, ferritic stainless steel with excellent oxidation resistance and brazing properties can be achieved.

[0103] In the ferritic stainless steel disclosed in Scheme 2, an alumina layer with alumina as the main component is formed by heating at 1050°C for 50 hours. When (C) is set as the thickness of columnar crystals 201 in the cross section when the alumina layer 20 is cut in the thickness direction, and (E) is set as the thickness of equiaxed crystals 202 in the cross section when the alumina layer 20 is cut in the thickness direction, the alumina layer satisfies the following formula (1) or can be 100% columnar crystals.

[0104] (C) / (E)≥1.2···(1)

[0105] Based on the above composition, ferritic stainless steels can achieve excellent oxidation resistance under high-temperature conditions. In particular, when the alumina layer is 100% columnar crystals, ferritic stainless steels with even better oxidation resistance can be achieved.

[0106] The ferritic stainless steel disclosed in Scheme 3 may further contain, in Scheme 1 or 2 above, one or more of the following by mass percent: Zr: less than 0.50%, V: less than 0.50%, Cu: less than 1.0%, Mo: less than 2.0%, W: less than 2.0%, Hf: less than 0.50%, Sn: less than 0.50%, Ta: less than 0.5%, Ti: less than 0.20%, Mg: less than 0.015%, and Ca: less than 0.015%.

[0107] The ferritic stainless steel involved in Scheme 4 of this disclosure is, in any of Schemes 1 to 3 above, when [Al] is set as % by mass of Al and [Nb] is set as % by mass of Nb,

[0108] It can also satisfy [Al] / (10×[Nb])<8.

[0109] The method for manufacturing ferritic stainless steel disclosed in Scheme 5 contains, by mass percent, C: 0.030% or less, Si: 0.01-1.5%, Mn: 0.01-1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0-25.0%, Al: 2.0-4.0%, Ni: 1.00% or less, Nb: 0.01-0.70%, N: 0.030% or less, B: 0.0003-0.01%, REM: 0.01-0.20%, with the remainder consisting of Fe and unavoidable impurities.

[0110] The final annealing process following the cold rolling process includes a first process in which the temperature is heated to a range of 900°C to 1200°C under an inert gas atmosphere and at a dew point below -40°C.

[0111] Based on the above structure, ferritic stainless steel with an Al-based oxide film of 8 nm or more and less than 20 nm on the surface can be manufactured. Therefore, ferritic stainless steel with excellent oxidation resistance and brazing properties can be manufactured.

[0112] The manufacturing method of ferritic stainless steel involved in Scheme 6 of this disclosure, in Scheme 5 above, may include a second process after the first process, which involves holding the stainless steel at a temperature range of 900°C to 1200°C for a period of no more than 5 minutes.

[0113] Based on the above structure, it is possible to manufacture ferritic stainless steel with an Al-based oxide film on the surface of 8 nm or more and less than 20 nm.

[0114] The manufacturing method of the ferritic stainless steel involved in Scheme 7 of this disclosure is to form an alumina layer mainly composed of alumina by heating the ferritic stainless steel obtained by the final annealing process in Scheme 5 or 6 above at 1050°C for 50 hours. When (C) is set as the thickness of columnar crystals 201 in the cross section when the alumina layer is cut in the thickness direction, and (E) is set as the thickness of equiaxed crystals 202 in the cross section when the alumina layer 20 is cut in the thickness direction, the alumina layer satisfies the following formula (1) or may be 100% columnar crystals.

[0115] (C) / (E)≥1.2···(1)

[0116] Based on the above composition, a ferritic stainless steel can be achieved that exhibits excellent oxidation resistance under high-temperature conditions. In particular, when the alumina layer is 100% columnar crystal, a ferritic stainless steel with brazing properties and even better oxidation resistance can be achieved.

[0117] The method for manufacturing ferritic stainless steel disclosed in Scheme 8 may further contain, in any of Schemes 5 to 7, one or more of the following by mass percentage: Zr: less than 0.50%, V: less than 0.50%, Cu: less than 1.0%, Mo: less than 2.0%, W: less than 2.0%, Hf: less than 0.50%, Sn: less than 0.50%, Ta: less than 0.5%, Ti: less than 0.20%, Mg: less than 0.015%, and Ca: less than 0.015%.

[0118] [Example]

[0119] To evaluate the physical properties of the ferritic stainless steel of the present invention, ferritic stainless steels with the compositions shown in Table 1 below were manufactured as inventive examples and comparative examples. In Table 1, steel grades No. 1 to 16 are ferritic stainless steels manufactured within the scope of the present invention and serving as examples of the present invention. Furthermore, steel grades No. 17 to 27 in Table 1 are ferritic stainless steels manufactured under conditions outside the scope of the present invention and serving as comparative examples.

[0120] When manufacturing steel products of the grades shown in Table 1, firstly, steel with the composition shown in Table 1 is vacuum melted to produce 30 kg slabs. These slabs are then heated at 1230°C for 2 hours and hot-rolled to produce hot-rolled plates with a thickness of 3 mm. The resulting hot-rolled plates are annealed between 900 and 1050°C to produce hot-rolled annealed plates. The hot-rolled annealed plates are then subjected to three cold rolling processes and intermediate annealing to produce cold-rolled plates with a thickness of 50 μm. The resulting cold-rolled plates are then subjected to final annealing under an inert gas atmosphere, according to the temperature, time, and dew point conditions shown in Table 2. For steel grades No. 1 to 27, a gas containing 70–90% H2 and 10–30% N2 or Ar is used as the aforementioned inert gas for final annealing.

[0121] Furthermore, cold rolling is performed with a rolling rate of 60-85%, and intermediate annealing after cold rolling is carried out at a temperature range of 900-1050°C. Also, the manufacturing method described in this embodiment is an example and is not limiting.

[0122] Table 1

[0123]

[0124] Table 2

[0125]

[0126] In Table 1, the composition of the components contained in each steel grade is expressed as mass % . Additionally, the remainder besides the components shown in Table 1 is Fe or unavoidably mixed small amounts of impurities (unavoidable impurities). The underlines in Table 1 indicate that the range of components contained in the stainless steels involved in the comparative examples of the present invention is outside the scope of the present invention.

[0127] (Measurement of film thickness)

[0128] The thickness of the Al-based oxide film in the present invention examples and comparative examples manufactured under the conditions shown in Tables 1 and 2 will be described below.

[0129] The thickness of the Al oxide film was measured using a glow discharge spectrophotometer (GDS) (HORIBA GD-Profiler2). Specifically, the Al concentration was measured at 0.0025 μm intervals from the surface of the 50 μm thick cold-rolled annealed sheet involved in the present invention and comparative examples to a depth of 0.1 μm. The GDS measurement conditions were as follows: gas replacement time: 200 s, pre-sputtering time: 30 s, background: 5 s, depth: 1.01 μm, pressure: 600 Pa, output: 35 W, RMS value: 8.75 W. Module: 8 V, phase: 4 V, frequency: 100 Hz, duty cycle: 0.25.

[0130] Furthermore, the thickness of the alumina film was determined by using the full width at half maximum (FWHM) of the oxygen peak concentration. The results are shown in Table 2 below. In Table 2, "〇 (Good)" indicates that the thickness of the alumina film is less than 20 nm, and "× (Poor)" indicates that the thickness of the alumina film is greater than 20 nm.

[0131] (Bonding performance evaluation test)

[0132] The following describes the brazing performance evaluation tests performed on the examples and comparative examples of the present invention shown in Tables 1 and 2. The brazing performance evaluation tests were conducted by cutting a JIS 13B test piece from a cold-rolled annealed sheet with a thickness of 50 μm into two halves. Specifically, the two halves were overlapped by 10 mm, and a 0.1 mm thick brazing filler metal (BNi-5: ASTM) was applied to one side of the contact surface (12.5 mm × 10 mm). Then, using an atmosphere heat treatment furnace, the overlapping samples were brazed at 1200°C in a vacuum (dew point -65°C) to join them. After joining, a tensile test was performed. The values ​​shown in Table 3 represent the tensile strength (MPa) at the point of fracture. A tensile strength of 250 MPa or higher indicates good brazing performance. Furthermore, in the tensile test, good brazing performance was determined when fracture occurred from the base material. Conversely, poor brazing performance was determined when fracture occurred from the brazed portion. For cases with good solderability, it is marked as "〇 (Good)" in Table 3. For cases with poor solderability, it is marked as "× (Poor)" in Table 3.

[0133] (Determination of the columnar / equiaxed crystal ratio in an alumina layer, which is mainly composed of alumina)

[0134] The following describes the determination of the columnar crystal / equiaxed crystal ratio of the alumina layer implemented in the embodiments and comparative examples of the present invention shown in Tables 1 and 2. First, the test piece was heated at 1050°C for 50 hours, then immersed in liquid nitrogen for 5 minutes, and immediately subjected to impact to break it. Then, the cross-section of the alumina layer was observed using a scanning electron microscope (SEM) SU5000 (manufactured by Hitachi High Technology Co., Ltd.) at a magnification of 20,000x, and the thickness (C) of the columnar crystals and the thickness (E) of the equiaxed crystals were measured, and the columnar crystal / equiaxed crystal ratio ((C) / (E)) was calculated.

[0135] In addition, the ratio of columnar crystals to equiaxed crystals was determined by SEM observation at a magnification of 20,000x, with measurements taken randomly at three locations, and the average value calculated. Furthermore, when equiaxed crystals do not form layers, the length of the grain size of an isolated equiaxed crystal is used to determine its thickness.

[0136] The results are shown in Table 3 below. In the determination of the columnar crystal / equiaxed crystal ratio of the alumina layer in Table 2, "○ (good)" indicates that the columnar crystal / equiaxed crystal ratio of the alumina layer is 1.2 or higher, and "× (bad)" indicates that the columnar crystal / equiaxed crystal ratio of the alumina layer is less than 1.2.

[0137] (High-Temperature Oxidation Resistance Evaluation Test)

[0138] The following describes the evaluation test of high-temperature oxidation resistance characteristics performed on the examples and comparative examples of the present invention shown in Tables 1 and 2. First, for each steel grade shown in Table 1, three test pieces, each 20 mm wide and 25 mm long, were collected from a cold-rolled sheet with a thickness of 50 μm as described in the steel manufacturing process. These test pieces were placed in an atmospheric atmosphere at 1050°C for 50 hours, and the average oxidation increment of the three pieces was measured. This evaluation test of high-temperature oxidation resistance characteristics was conducted in an atmospheric atmosphere using an Elema electric furnace. The results are shown in Table 3 below. In the determination of high-temperature oxidation resistance characteristics in Table 3, "○ (Good)" indicates an average oxidation increment of 1 mg / cm³. 2 Below, "× (adverse)" indicates that the concentration exceeds 1 mg / cm³. 2 .

[0139] Table 3

[0140]

[0141] As shown in the column of Al oxide film thickness in Table 3, the Al oxide films of the inventive steel grades No. 1 to 16 manufactured according to the manufacturing method within the scope of the present invention are all less than 20 nm thick and have good solderability.

[0142] In contrast, the Al oxide film thickness of comparative steel grades No. 17-18, 21, 23 and 25-27 is more than 20 nm, and their brazing properties are low.

[0143] Furthermore, the results in the Al oxide film thickness column of Table 3 confirm that ferritic stainless steels with an Al oxide film thickness of less than 20 nm have excellent brazing properties.

[0144] Furthermore, as shown in the column of the oxidation resistance results in Table 3, it is confirmed that all of the invention steel grades No. 1 to 16, which were heated at 1050°C for 50 hours in the final annealing process, showed good oxidation resistance.

[0145] Furthermore, the results from the columnar crystal / equiaxed crystal ratio of 3 and the results from the oxidation resistance column confirm that when the columnar crystal / equiaxed crystal ratio is 1.2 or higher, the high-temperature oxidation resistance is good.

[0146] That is, it has been confirmed that when ferritic stainless steel within the scope of this invention is heated at 1050°C for 50 hours, it exhibits excellent brazing properties and oxidation resistance.

[0147] The reasons why comparative steel grades No. 17 to 27 did not show better results than the steel grades of the present invention will be explained below.

[0148] Comparative steel grade No. 17 has a Mn content of more than 1.0%, which results in reduced high-temperature oxidation resistance. Furthermore, comparative steel grade No. 17 has a B content of less than 0.0003%, which reduces secondary machinability and does not show good results regarding brazing properties.

[0149] Comparative steel grade No. 18, due to its REM content being less than 0.01% and Ti content being more than 0.20%, is prone to equiaxed crystallization and therefore does not show excellent high-temperature oxidation resistance.

[0150] Comparative steel grade No. 19, with a Nb content below 0.01%, is prone to degradation in high-temperature oxidation resistance and workability, and therefore did not show excellent results in high-temperature oxidation resistance. On the other hand, comparative steel grade No. 19, with a Ti content below 0.20%, showed good results in terms of brazingability.

[0151] Comparative steel grade No. 20, lacking Ti content, is less prone to forming Ti-based oxides, thus exhibiting good brazing properties. On the other hand, comparative steel grade No. 20, with a Zr content exceeding 0.50%, tends to segregate Zr at alumina grain boundaries, promoting equiaxed crystallization.

[0152] Comparative steel grade No. 21 has a Si content of more than 1.5%, and due to the influence of Si-based oxides such as SiO2, it exhibits excellent resistance to high-temperature oxidation. In contrast, comparative steel grade No. 21, due to its Si content of more than 1.5%, forms Si-based oxides, and therefore does not show good results regarding brazing properties.

[0153] Comparative steel grade No. 22, due to its Al content being less than 2.0%, has difficulty forming an Al2O3 oxide film, thus showing good results in terms of brazing performance. However, it did not show good results in terms of high-temperature oxidation resistance.

[0154] Comparative steel grade No. 23, due to its Ti content being higher than 0.20%, forms Ti oxides such as TiO2, and therefore did not show good results regarding high-temperature oxidation resistance and brazing properties.

[0155] Comparative steel grade No. 24, due to its Nb content being higher than 0.70%, is prone to equiaxed crystallization, and therefore did not show good results regarding high-temperature oxidation resistance.

[0156] Comparative steel grade No. 25, due to its Al content being higher than 4.0%, easily forms an Al2O3 oxide film, thus showing good results in terms of high-temperature oxidation resistance. However, it did not show good results in terms of brazing properties.

[0157] Comparative steel grade No. 26 has a Cr content higher than 25.0%, which leads to Cr concentration at the alumina grain boundaries, making it easier to form equiaxed crystals. Furthermore, since the Ti content in Comparative steel grade No. 26 is higher than 0.20%, Ti oxides such as TiO2 are formed. Therefore, Comparative steel grade No. 26 did not show good results regarding high-temperature oxidation resistance and brazing properties.

[0158] Comparative steel grade No. 27 showed good results regarding high-temperature oxidation resistance because its REM content was greater than 0.20%. However, because the REM content of Comparative steel grade No. 27 was greater than 0.20%, it formed oxides such as Y2O3 or CeO2, and therefore did not show good results regarding brazing properties.

[0159] (Appendix Items)

[0160] This invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included within the technical scope of this invention.

[0161] Explanation of symbols

[0162] 1. Ferritic stainless steel

[0163] 20 Alumina Layer

[0164] 201 columnar crystals

[0165] 202 isometric crystal

[0166] Thickness of C columnar crystals

[0167] E-type equiaxed crystal thickness

Claims

1. Ferritic stainless steel, containing, by mass%, less than 0.030% C, 0.01-1.5% Si, 0.01-1.00% Mn, less than 0.050% P, less than 0.005% S, 15.0-25.0% Cr, 2.0-4.0% Al, less than 1.00% Ni, 0.01-0.70% N, less than 0.030% N, 0.0003-0.01% B, and 0.01-0.20% REM, with the remainder consisting of Fe and unavoidable impurities, and having an Al-based oxide film on the surface with a thickness of more than 8 nm and less than 20 nm.

2. The ferritic stainless steel according to claim 1, wherein an alumina layer mainly composed of alumina is formed by heating at 1050°C for 50 hours, if (C) is set as the thickness of columnar crystals in the cross section when the alumina layer is cut in the thickness direction, and (E) is set as the thickness of equiaxed crystals in the cross section when the alumina layer is cut in the thickness direction, then the alumina layer satisfies the following formula (1). (C) / (E)≥1.2···(1) Or it may be 100% columnar crystals.

3. The ferritic stainless steel according to claim 1 or 2, further comprising, by mass%, one or more of the following: Zr: less than 0.50%, V: less than 0.50%, Cu: less than 1.0%, Mo: less than 2.0%, W: less than 2.0%, Hf: less than 0.50%, Sn: less than 0.50%, Ta: less than 0.5%, Ti: less than 0.20%, Mg: less than 0.015%, and Ca: less than 0.015%.

4. The ferritic stainless steel according to claim 1 or 2, wherein when [Al] is set as the mass percentage of Al and [Nb] is set as the mass percentage of Nb, [Al] / (10×[Nb]) < 8.

5. A method for manufacturing ferritic stainless steel, comprising, by mass %: C: less than 0.030%, Si: 0.01–1.5%, Mn: 0.01–1.00%, P: less than 0.050%, S: less than 0.005%, Cr: 15.0–25.0%, Al: 2.0–4.0%, Ni: less than 1.00%, Nb: 0.01–0.70%, N: less than 0.030%, B: 0.0003–0.01%, REM: 0.01–0.20%, with the remainder consisting of Fe and unavoidable impurities, the method comprising a cold rolling process and a final annealing process following the cold rolling process, the final annealing process comprising a first process of heating to a temperature range of 900°C–1200°C under an inert gas atmosphere at a dew point below -40°C.

6. The method for manufacturing ferritic stainless steel according to claim 5, wherein the final annealing process includes a second process following the first process, wherein the temperature is maintained at a range of 900°C to 1200°C for a period of no more than 5 minutes.

7. The method for manufacturing ferritic stainless steel according to claim 5 or 6, wherein the ferritic stainless steel obtained after the final annealing process forms an alumina layer mainly composed of alumina when heated at 1050°C for 50 hours, wherein (C) is defined as the thickness of columnar crystals in the cross-section when the alumina layer is cut in the thickness direction, and (E) is defined as the thickness of equiaxed crystals in the cross-section when the alumina layer is cut in the thickness direction, the alumina layer satisfies the following formula (1). (C) / (E)≥1.2···(1) Or it may be 100% columnar crystals.

8. The method for manufacturing ferritic stainless steel according to claim 5 or 6, wherein the ferritic stainless steel further comprises, by mass%, one or more of the following: Zr: less than 0.50%, V: less than 0.50%, Cu: less than 1.0%, Mo: less than 2.0%, W: less than 2.0%, Hf: less than 0.50%, Sn: less than 0.50%, Ta: less than 0.5%, Ti: less than 0.20%, Mg: less than 0.015%, and Ca: less than 0.015%.

Citation Information

Patent Citations

  • Fe-Cr-Al BASED ALLOY FOIL HAVING EXCELLENT OXIDATION RESISTANCE AND HIGH TEMPERATURE DEFORMATION RESISTANCE, AND PRODUCTION METHOD THEREFOR

    JP2003105506A

  • Stainless steel foil and method for producing the same

    JP2011032524A

  • Stainless steel sheet and stainless steel foil

    CN104870675A

  • Al-CONTAINING HEAT-RESISTANT FERRITIC STAINLESS STEEL SHEET SUPERIOR IN WORKABILITY AND OXIDATION RESISTANCE, AND MANUFACTURING METHOD THEREFOR

    JP2004307918A